IMPLEMENTASI AKAD MURABAHAH PADA PEMBIAYAAN KPR DI BANK TABUNGAN NEGARA SYARIAH PAREPARE - Fitri Handayani; Rahman Ambo Masse; Sunuwati Sunuwati (Institut Agama Islam Negeri Parepare, 2019)
This study discusses the implementation of murabahah contracts on mortgage financing in the Parepare Islamic state savings bank. That the BTN Syariah bank is a unit of conventional Bank BTN which raises doubts about mortgage financing, whether or not it has implemented murabahah contracts in mortgage financing or not. As recommended by the DSN fatwa and Indonesian banks. This study aims to determine the implementation of the murabahah contract on mortgage financing at the Parepare Syariah State Savings Bank. The results of this study indicate that: (1) the financing mechanism for mortgages at Bank BTN Syariah Parepare is in accordance with the rules of banks and government, the rules governed by the government are the rules regarding subsidized mortgages stipulated in PermenPUPR Number 21 / PRT / M / 2016 concerning convenience and or assistance in obtaining houses for low income people. PermenPUPR Number 26 / PRT / M / 2016 concerning changes to the ministerial regulations on public works and public housing number 21 / PRT / M / 2016 and PermenPUPR Republic of Indonesia Number 425 / KPTS / M / 2015 concerning limits on house selling prices that can be obtained through credit or financing of prosperous home ownership. (2) Implementation of murabahah contract at BTN Syariah Parepare bank, terms and conditions are in accordance with the principle of murabahah contract, murabahah contract has not implemented well on mortgage products at BTN Syariah Parepare bank due to the existence of murabahah contract elements which are not in accordance with the fatwa of the board national sharia-MUI. The element of the murabahah contract that is not in accordance with the DSN-MUI fatwa is the down payment and rescheduling. The elements of the murabahah contract are in accordance with the DSN-MUI fatwa, namely discounts, settlement of accounts receivable, fines and accelerated repayments.